The Influence of Product Quality and Customer Satisfaction on Purchasing Decisions at UD Kita Maju (Surya Mas Housing Complex) - Kesuma, Jeniffer; Arwin (Cattleya Darmaya Fortuna, 2023)
UD. Kita Maju is a company engaged in the property sector and has done a lot of housing developments, especially in the city of Kisaran. The purpose of this study was to determine the effect of product quality and customer satisfaction on purchasing decisions at UD Kita Maju (Surya Mas Housing Complex).The research method that the authors use in this study is a quantitative method, namely research that aims to determine the relationship between two or more variables and determine their effect. The total population in this study were 30 consumers of the Surya Mas housing complex.From the results of the determination coefficient, it can be seen that the R Square value (R2) or the determination coefficient obtained is 0.558, meaning that the Purchase Decision variable can be explained by the Product Quality and Customer Satisfaction variables of 55.8% while the remaining 44.2% is influenced by other factors that come from from outside this research model such as consumer loyalty and consumer trust. the results of partial hypothesis testing using the t-test, it is known that the Product Quality variable has a tcount (3,743) > ttable (2.048) with a significant level of 0.001 <0.05 so it can be concluded that there is a partially significant positive effect between Product Quality on Buying decision. Customer satisfaction has a tcount (2.651) > ttable (2.048) with a significant level of 0.013 <0.05 so it can be concluded that there is a partially significant positive effect between customer satisfaction on purchasing decisions. Product Quality and Customer Satisfaction have Fcount (17,056) > Ftable (3.34) with a significant level of 0.000 <0.05 so it can be concluded that there is a partially significant positive effect between Product Quality and Customer Satisfaction on Purchasing Decisions.